The effect of social media uses on mental health: study among health vocational student at Universitas Esa Unggul, Jakarta, Indonesia - Fannya, Puteri; Indawati, Laela; Putra, Daniel H. (International Journal Of Community Medicine And Public Health, 2024)
Background: Social media has growth significantly in terms of quality, consumption, and quantity. Social media consumers have made online social communication an important part of their daily lives, as evidenced by the increasing number of daily users. Many studies on the effects of social media have been conducted, and it has been found that frequent use of social media sites can be linked to negative symptoms and indicators of depression, anxiety, and stress. The purpose of this study is to determine the impact of social media use on the mental health of vocational students at the Faculty of Health Sciences, Esa Unggul University. Methods: This study used a cross-sectional design with a Chi-square test. Data were collected using the General Health Questionnaire 12 (GHQ-12) to assess mental health levels. Data on characteristics and social media usage behaviour were collected by asking a series of questions through a questionnaire. Results: The results of this study showed that 60.2% of the 108 respondents used 3-4 social media applications. A total of 47.2% of respondents accessed social media for more than 4 hours per day, and only 22.2% accessed social media for less than 2 hours per day. There was a significant relationship between the duration of social media use and mental health levels (p value=0.001). Meanwhile, there was no significant relationship between the number of applications used and mental health levels (p value=0.475). Conclusions: Based on the above study results, it is expected that students can limit the intensity of their daily social media use.